Exogenous α-synuclein fibrils seed the formation of Lewy body-like intracellular inclusions in cultured cells - Luk, Kelvin C. (National Academy of Sciences, 2009)
Cytoplasmic inclusions containing α-synuclein (α-Syn) fibrils, referred to as Lewy bodies (LBs), are the signature neuropathological hallmarks of Parkinson's disease (PD). Although α-Syn fibrils can be generated from recombinant α-Syn protein in vitro, the production of fibrillar α-Syn inclusions similar to authentic LBs in cultured cells has not been achieved. We show here that intracellular α-Syn aggregation can be triggered by the introduction of exogenously produced recombinant α-Syn fibrils into cultured cells engineered to overexpress α-Syn. Unlike unassembled α-Syn, these α-Syn fibrils “seeded” recruitment of endogenous soluble α-Syn protein and their conversion into insoluble, hyperphosphorylated, and ubiquitinated pathological species. Thus, this cell model recapitulates key features of LBs in human PD brains. Also, these findings support the concept that intracellular α-Syn aggregation is normally limited by the number of active nucleation sites present in the cytoplasm and that small quantities of α-Syn fibrils can alter this balance by acting as seeds for aggregation.